Quantifying promoter‐specific Insulin‐like Growth Factor 1 gene expression by interrogating public databases. Issue 1 (3rd January 2019) - Rotwein, Peter
Abstract: The actions of insulin‐like growth factor 1 (IGF1), a small, secreted protein, are essential for normal somatic growth in children and are important for tissue regeneration and repair in adults. Similar functions are conserved in other mammalian species. IGF1 gene regulation is complicated in mammals, with transcription being controlled by different hormonal, nutritional, and tissue‐specific inputs. Quantifying IGF1 gene expression in different organs and tissues also has been difficult because of the variable contributions of its two promoters and because of the lack of standard platforms for analysis. Here, I have taken advantage of the wealth of information found in publicly accessible RNA‐sequencing libraries to measure steady‐state levels of IGF1 mRNAs from human and macaque, species chosen because they are not readily tractable experimental organisms, yet retain similar IGF1 gene organization. Results demonstrate that IGF1 transcripts are highly expressed in fat and liver in both species, and are induced during human adipocyte differentiation. IGF1 mRNAs also are increased in macaque skeletal muscle after selected dietary manipulations. In the organs and tissues examined, IGF1 promoter 1 appears to be far more active than promoter 2. Collectively, these observations show that interrogating large‐scale public genomic resources is an effective strategy for quantifying gene expression across different tissues and species. Abstract : Publicly accessible RNA‐sequencing libraries have been accessed to measure steady‐state levels of IGF1 mRNAs from human and macaque, species chosen because they are not readily tractable experimental organisms, yet retain similar IGF1 gene organization. Results show that IGF1 transcripts are highly expressed in fat and liver in both species, and are induced during human adipocyte differentiation. Interrogating large‐scale public genomic resources is an effective strategy for quantifying gene expression across different tissues and species.